Inquiry-Based Instruction Enhances Critical Thinking Skills in Elementary Social Studies Education - Ratnasari; Dina Febrianti (Journal of Innovation and Research in Primary Education, 2026)
Critical thinking skills remain underdeveloped in Indonesian elementary Social Studies education due to persistent teacher-centered pedagogical approaches that limit student engagement in analytical and evaluative reasoning processes. This study investigated the effect of inquiry-based instruction on fourth-grade students' critical thinking skills in Social Studies learning at SD Negeri Tepung Sari. A quasi-experimental one-group pretest-posttest design was employed with 29 fourth-grade students (ages 9-10) selected through purposive sampling. Participants engaged in four 90-minute inquiry-based learning sessions over two weeks, investigating authentic local social phenomena. Critical thinking skills were assessed using a researcher-developed essay instrument validated by expert review (Cronbach's α = 0.82) and aligned with Facione's five-dimension framework: interpretation, analysis, evaluation, inference, and explanation. Data were analyzed using descriptive statistics, paired-samples t-test, and normalized gain (N-Gain) calculations. The intervention produced statistically significant improvements in critical thinking performance (pretest M = 52.00, posttest M = 78.00; t = 17.50, p < .001) with medium effect size (N-Gain = 0.54). Categorical analysis revealed 89.7% of students achieved proficient or advanced levels post-intervention compared to 6.9% initially, while all five critical thinking dimensions demonstrated uniform gains of 8-9 percentage points. Inquiry-based instruction significantly enhances elementary students' critical thinking skills in Social Studies, validating constructivist pedagogy effectiveness in Indonesian educational contexts and supporting Merdeka Curriculum implementation.